Adding Mandarin Orange Peel Extract to the Vegetable Jam's Attributes - Tyastiningrum, Elisabeth; Aini, Nur; Wuryatmo, Erminawati (Universitas Pattimura, 2023)
Indonesians still do relatively little to prepare and consume veggies. Products made from vegetable raw materials that have the potential to be developed is a jam. Making vegetable jam with a combination of several types of vegetables can make the flavor of the jam less favorable. So, efforts are required to add mandarin orange peel extract, which includes essential oils and possibly intense limonene components as a taste, to make up for the deficits arising from the flavor aspect and enhance the intrinsic quality of the jam. This study sought to identify the best treatment and compare it to a control, as well as the effect of adding orange peel extract and the difference in concentration added to the sensory properties of vegetable jam. It also sought to identify the best treatment and examine vegetable jam's physicochemical and microbiological properties. This study employed a factorial, totally randomized design as its methodology. Mandarin orange peel extract treatment without encapsulation (E1) and encapsulated orange peel extract made up the first factor (E2). The concentration that was added to the vegetable jam, consisting of 0.5% (K1), 1% (K2), 1.5% (K3), 2% (K4), and 2.5%, is the second factor (K5). According to the analysis of variance, adding orange peel extract in varying concentrations greatly affected the aroma, taste, and overall preference. Still, it had no discernible impact on the color characteristics or lubricating power. The E2K4 treatment produced the greatest results for the sensory properties of the jam when compared to controls using a paired T-test. This significantly changed overall preference, water content, water activity, antioxidant activity, pH, and TPC. Yet, it had little impact on color saturation.